2022
DOI: 10.3389/fnins.2022.821179
|View full text |Cite
|
Sign up to set email alerts
|

Increased Excursions to Functional Networks in Schizophrenia in the Absence of Task

Abstract: Schizophrenia is a chronic psychotic disorder characterized by the disruption of thought processes, perception, cognition, and behaviors, for which there is still a lack of objective and quantitative biomarkers in brain activity. Using functional magnetic resonance imaging (fMRI) data from an open-source database, this study investigated differences between the dynamic exploration of resting-state networks in 71 schizophrenia patients and 74 healthy controls. Focusing on recurrent states of phase coherence in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(119 reference statements)
2
13
0
Order By: Relevance
“…In functional magnetic resonance imaging (fMRI) studies, traditional brain network construction methods are generally during the resting-state. Current dynamic network analyses have confirmed that fluctuations in functional connections exist, which has attracted increasing attention in the academic world [ 5 , 6 ]. Studies have shown that dynamic network analysis can better detect fluctuations in the brain’s functional connections.…”
Section: Introductionmentioning
confidence: 99%
“…In functional magnetic resonance imaging (fMRI) studies, traditional brain network construction methods are generally during the resting-state. Current dynamic network analyses have confirmed that fluctuations in functional connections exist, which has attracted increasing attention in the academic world [ 5 , 6 ]. Studies have shown that dynamic network analysis can better detect fluctuations in the brain’s functional connections.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify recurrent spatiotemporal patterns of phase-locking–henceforth called ‘LEiDA modes’–we performed k-means clustering on the phase-locked time-series of each of the datasets that were analyzed (HCPEP CONx4, HCPEP NAPx4, Cobre CONx1, Cobre SCHZx1, see Materials and methods ). This is similar to a previous study [ 47 ], but different from other studies that used LEiDA where k-means clustering was either performed on concatenated datasets across groups [ 54 56 ] or where the centroids extracted from one group were used to seed the clustering of other groups [ 57 59 ]. The approach in this study considers each dataset as a unique observation of brain activity with associated variability in the spatiotemporal modes and avoids data leakage which occurs when dimensionality reduction is performed on the dataset as a whole [ 60 ].…”
Section: Resultsmentioning
confidence: 63%
“…Effect sizes were negligible to small ( d = -0.11 to d = 0.36) for early disorder subjects (NAP group) and moderate to large ( d = -0.58 to d = -0.82) for subjects with established schizophrenia (SCHZ group) (see S2 Table ). Previous discrimination analysis on the same Cobre dataset using a distance measure between patterns of instantaneous phase synchrony reported a moderate effect size ( d = 0.67) [ 33 ], as did another study using the mean probability of dwell time in a global state (Hedge’s g = 0.73) [ 56 ]. In contrast, one study reported significantly lower effect sizes ( d = 0.06 to d = 0.31) using measures of metastability in its original form, and using measures of between-network FC ( d = 0.04 to d = 0.52) [ 68 ].…”
Section: Discussionmentioning
confidence: 92%
“…Previous evidence has suggested that the LEiDA framework is highly flexible, robust, and precise ( Glerean et al, 2012 ; Ponce-Alvarez et al, 2015 ; Cabral et al, 2017 ), allowing for recurrent states that were detected and characterized in resting state and task conditions in the healthy brain. It can also distinguish the abnormal brain states in psychiatric diseases, such as schizophrenia ( Farinha et al, 2022 ), major depressive disorders ( Figueroa et al, 2019 ; Alonso Martínez et al, 2020 ; Wang et al, 2022 ), and trait self-reflectiveness ( Larabi et al, 2020 ), and the alteration of brain states in psilocybin ( Lord et al, 2019 ) and sleep ( Deco et al, 2019 ). The fundamental framework of LEiDA is shown in Figure 1 , and the detailed steps are mentioned later.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study indicated that the dynamic properties of recurrent FC states are related to cognitive performance in healthy participants ( Cabral et al, 2017 ). Meanwhile, the PL patterns obtained from the LEiDA approach have shown particular sensitivity to alterations in psychiatric symptoms, such as schizophrenia ( Farinha et al, 2022 ) and major depressive disorders ( Figueroa et al, 2019 ; Alonso Martínez et al, 2020 ; Wang et al, 2022 ). However, the recurrent PL patterns identified by LEiDA in ASD have not yet been qualitatively probed.…”
Section: Introductionmentioning
confidence: 99%